Battle angel : an Immortal city novel - Speer, Scott, 1982- (Razorbill, an imprint of Penguin Group (USA), 2014)
Jackson tests the strength of his bond with Maddy while struggling to find forgiveness to protect Immortal City from a demon invasion.